Developing sustainable food-based dietary guidelines for Lebanon: integrating health, economic resilience, and sustainability - Nahla Hwalla; Nour Deeb; Farah Naja; Farah Naja; Lara Nasreddine (Frontiers in Sustainable Food Systems)
BackgroundDeveloping Sustainable Food-Based Dietary Guidelines (SFBDGs) aligned with sustainable healthy diets (SHDs) is critical for addressing food and nutrition insecurity, mitigating diet-related diseases, improving public health, and promoting environmental sustainability. Lebanon, a low-middle-income Eastern Mediterranean country, faces significant challenges including high prevalence of food insecurity, wide-spread noncommunicable diseases, limited natural resources and ongoing economic, social and environmental crises.ObjectiveTo develop culture-specific SFBDGs for Lebanon aligned with recommendations for SHDs, integrating nutrition, health, economic, and environmental factors.MethodsThe SFBDGs were formulated using a diet optimization mathematical tool, Optimeal®, which generates patterns resembling current diets while satisfying nutritional, health, cost, and environmental footprint (EFP) constraints. Data from the latest national food consumption survey of Lebanese adults served as the reference for current food consumption pattern. Nutritional and health constraints were based on EAT-Lancet and World Health Organization (WHO) recommendations and Dietary Reference Intakes (DRIs). Cost constraints were maximized to match the cost of food groups within the current consumption pattern, while EFP constraints were based on the environmental impact of these food groups. The optimized consumption was later translated into SFBDGs.ResultsCompared to current national consumption, the optimized diet recommended increases in whole grains (+287%), dairy products (+61%), legumes (+50%), and fish (+26%) and reductions in refined grains (−66%), red meat (−65%), poultry (−32%), and added sugars and fresh fruit juices (−12%). Diet optimization led to a reduction in calorie intake (−6%) and EFPs, including greenhouse gas emissions (−24%), energy use (−7%), and water use (−6%), while maintaining cost.ConclusionThe developed optimized diet and resulting Lebanese SFBDGs addressed nutrition, health, economic, and environmental sustainability of current food consumption pattern, providing a scientific foundation for policies promoting SHDs that are affordable and culture-specific, which can mitigate food insecurity and malnutrition and alleviate some of the country’s challenges.